Emulsões de azeite de oliva com isolado proteico de ervilha para formulação de margarina clean label - Nascimento, Fernando Henrique (2024)
Margarine stands out for its history of changes in composition and processes aimed at improving its sensorial and nutritional quality. Eliminating trans fatty acids (TFAs) and reducing saturated (SFAs) to reduce proven risks to consumer health is a research focus nowadays. The trend towards clean label consumption and regulatory pressures from the markets reinforce the urgency of this new change. The development of edible emulsions emerges as an alternative as it allows the structuring of oils rich in mono- and polyunsaturated fatty acids (MUFA and PUFA), replacing additives and SFAs with new natural structures, such as protein micro-particles. The pea protein isolate (PPI) can be denatured, cross-linked and micro-particulated through physical and enzymatic processes to formulate emulsions. Extra virgin olive oil is a source of monounsaturated fatty acids and natural antioxidants, making it a healthy choice with oxidative stability. Using these two ingredients, emulsions were formulated with the aim of modeling clean label margarine bases. These emulsions were structured using Pickering emulsions, employing microparticles of denatured pea protein isolate that were sonicated using high-intensity ultrasound, with and without prior cross-linking by microbial transglutaminase. A full factorial design was used to study the effects of the following factors over 20 days: pH (ranging from 3 to 8), aqueous fraction (from 0.3 to 0.4), and protein concentration in the aqueous phase (from 5% to 10%). The emulsions containing 10% protein in the aqueous phase, at pH 8, and with an aqueous fraction of 0.3 to 0.4 (by volume), exhibited greater stability, firmness, and consistency. Denatured PPI samples were also characterized by Fourier Transform Infrared (FTIR) spectroscopy, revealing that changes in the secondary structure due to enzymatic cross-linking altered the emulsifying properties of the protein. These results formed the basis for a Central Composite Rotatable Design (CCRD) to model formulations regarding texture stability, oil retention, oil phase quality, and morphology. The obtained models demonstrated that heat-denatured PPI stabilizes firm and consistent emulsions with an aqueous fraction ranging from 0.25 to 0.30 and a protein concentration of 3% to 12%. Additionally, the olive oil maintained stability against oxidation during the 20-day storage period.